Effectiveness of food subsidies in raising healthy food consumption: Public distribution of pulses in India - Chakrabarti, Suman; Kishore, Avinash; Roy, Devesh (Oxford University Press, 2018)
This paper provides evidence on the effectiveness of one of the most common policies to improve nutrition among the poor, that is, a food subsidy. We study the case of subsidies on pulses in select Indian states and their impact on consumption and ultimately nutrition (protein intake). As a natural experiment, we use the introduction of pulses into India’s Public Distribution System (PDS) where the variations in prices were brought about by the inclusion of pulses in the PDS in some states and not in others.